Mechanism and Process of the Intermetallic Compound Particles Reinforced TiAl/Steel Brazing Seam. Issue 9 (September 2015) - Yulong, Li; Cheng, Zhao; Xiaowu, Hu; Jicai, Feng; Peng, He
Abstract: In order to prevent the formation of large size intermetallic compounds during the TiAl-based alloy brazing, a specially designed heating process, which was established based on the analysis of Ti-Al-Ag ternary phase diagram, was presented and validated. The associated mechanism and process were proposed as follows: (i) a special dwell period was installed at the early stage during the melting of the filler metal for the generation of a weak primary AlCu2 Ti intermetallic layer; (ii) with initial heating up, Ag atoms in the filler would diffuse into the TiAl substrate through the weak AlCu2 Ti layer and a new liquid phase of Ti-Al-Ag would form due to the combined effects of thermal disturbance, convection and concentration gradient; (iii) the primary intermetallic compounds would be broken into irregular particles and pieces which were pushed into the molten filler; (iv) with heating up to the peak temperature, the intermetallic particles would disperse uniformly in the brazing seam, resulting in a brazing seam with a dispersive distribution of the intermetallic compound particles. To verify the feasibility of the proposed method, the vacuum brazing of a TiAl-based alloy and a 42CrMo steel was conducted within a temperature range of 1033∼1173 K and a brazing time range of 100∼300 s. Microstructures of the brazed joints were examined by optical microscopy, scanning electron microscopy (SEM) as well as energy dispersive spectrum (EDS). The results show that an intermetallics particles reinforced TiAl/steel brazing seam can be obtained by the proposed heating process.